Body image issues among school going adolescent girls in a rural area of Haryana: a cross sectional study - ., Vinay; Kumar, Neelam; Malik, J. S.; Sachdeva, Aman (International Journal Of Community Medicine And Public Health, 2021)
Background: Adolescent girls in today’s world are extremely conscious of perceptions of a perfect body. With the growing sense of thin ideal body image during adolescence, they try to lose body weight to attain the perfect body size. The emphasis on thinness and on an ideal female body shape and size is physically and psychologically detrimental to the health of many young women. This study was carried out with objective to find the prevalence of body image issue among adolescent girls in rural area. Methods: This cross-sectional study was conducted in block Lakhanmajra, district Rohtak, Haryana. Adolescent girls in age group 13-19 years studying in class 8 to class 12 in 10 government and private senior secondary schools of Lakhanmajra block were included in the study. The total sample of 500 students was included in the study. A pre-designed pre-tested semi-structured interview schedule was used, and the responses were recorded by the investigator herself. Results: The findings of the present study show that 20.2% adolescent girls did not like their appearance when they look in the mirror and thus had body image dissatisfaction. 88.0% adolescent girls were satisfied with their weight and 12.0% were dissatisfied. 80.0% of the study subjects who were dissatisfied with their body weight had normal age specific BMI values. Only 20% of the adolescent girls who were not satisfied with their weight were underweight or overweight. Conclusions: More worries and less satisfaction about body image are found in girls. The relatives, the media, the peers and the community all have an impact on body shape satisfaction. But the greatest influence is that of the media and the community through standardising a thin ideal for female beauty.